Pengaruh Cita Rasa Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Mie Gacoan Cikampek Karawang - Pitriyani, Uju; Maulana, Asep (Jurnal Mirai Management, 2023)
In this day and age, many culinary businesses have sprung up with all their privileges and advantages. This culinary business is very popular with all people, especially millennials. Spicy culinary businesses that are in great demand and visited in Indonesia, one of which is Mie Gacoan. Mie Gacoan opened a new branch in Karawang City, namely in the Cikampek area. The purpose of this study was to determine the effect of taste and service quality on consumer satisfaction Mie Gacoan Cikampek. This research is a type of quantitative research with a descriptive approach. This study used samples taken from a predetermined population of 100 respondents. The population in this study were consumers of Mie Gacoan, Cikampek Karawang branch. In this study the technique used was probability sampling with the method used, namely Simple Random Sampling. Data collection techniques were surveyed using questionnaires and all variables in this study were measured using 5 (five) Likert scale. The data processing technique for the results of this research is by using the IBM SPSS Statistics 25 application, namely by testing validity, reliability testing, and multiple linear regression tests. The results showed that the taste variable did not have a significant effect on consumer satisfaction. While the service quality variable has a significant influence on customer satisfaction. Keywords: Taste, Service Quality, Consumer Satisfaction.